Single cycle to failure in torsion of three standard and five locking plate constructs - Cabassu, J. B.; Kowaleski, M. P.; Shorinko, J. K.; Blake, C. A.; Gaudette, G. R.; Boudrieau, R. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2011)
Objectives: The biomechanical properties of standard plates and recently designed locking plates were compared in torsion. We hypothesized that titanium (Ti) constructs would have the greatest deformation, and String of Pearls (SOP) constructs the greatest strength and stiffness.Methods: Dynamic compression plates (DCP), stainless steel (SS) limited contact (LC)-DCP, Ti LC-DCP, locking compression plate (LCP), 10 mm and 11 mm Advanced Locking Plate System (ALPS) 10 and 11, SOP and Fixin plates were applied to a validated bone model simulating a bridging osteosynthesis. Yield torque (strength), yield angle (deformation) and stiffness were compared using one-way ANOVA with post hoc Tukey (p <0.05).Results: The ALPS 11 constructs had significantly greater elastic deformation than all constructs except for the ALPS 10. There were not any differences in strength observed except for the ALPS 10 constructs, which was less than that for the SOP, LCP, DCP and ALPS 11 constructs. No differences in construct torsional stiffness were observed with the SS LCDCP, DCP, LCP and SOP constructs however all had greater stiffness than all remaining constructs. The ALPS 10 construct had lower stiffness than all constructs.Clinical significance: Modulus of elasticity of Ti explains the higher deformation and lower stiffness of these systems, with similar results for the Fixin due to its lower section modulus compared to all other plates. The SOP and standard constructs had surprisingly similar biomechanical properties in torsion. The rationale for selecting these implants for fracture repair likely needs to be based upon their differing biomechanical properties inherent to the diverse implant systems.Presented at the 38th Annual Conference of the Veterinary Orthopedic Society, Snowmass, Colorado, USA March 6, 2011.
Keywords: Torsion; bone plates; locking plates; in vitro; plate failure